2014
DOI: 10.5830/cvja-2014-012
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide poisoning increases Tpeak-Tend dispersion and QTc dispersion : cardiovascular topic

Abstract: SummaryObjectiveCarbon monoxide (CO) poisoning leads to cardiac dysrhythmia. Increased heterogeneity in ventricular repolarisation on electrocardiogram (ECG) shows an increased risk of arrhythmia. A number of parameters are used to evaluate ventricular repolarisation heterogeneity on ECG. The aim of our study is to investigate the effect of acute CO poisoning on indirect parameters of ventricular repolarisation on ECG.MethodsSixty-seven patients were included in this case–control study. Thirty patients with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Acute CO poisoning frequently affects the repolarisation of myocardium electrophysiology, resulting in abnormal ECG findings such as QTc prolongation and QTc dispersion [ 16 , 18 , 19 , 24 ]. These changes may lead to life-threatening cardiac arrhythmia or proarrhythmia effects [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute CO poisoning frequently affects the repolarisation of myocardium electrophysiology, resulting in abnormal ECG findings such as QTc prolongation and QTc dispersion [ 16 , 18 , 19 , 24 ]. These changes may lead to life-threatening cardiac arrhythmia or proarrhythmia effects [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This subsequently resulted in prolongation of the action potential and the associated intracellular Ca2 + transients, leading to disruption of ventricular myocyte repolarisation and QT prolongation [ 2 , 15 ]. Studies have also suggested that prolonged QTc and QTc dispersion increased the risk of atrial and ventricular arrhythmia in patients with CO poisoning [ 2 , 16 ]. However, no study has linked QTc interval or QTc dispersion with the prediction of DNS in patients with CO poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…CO has been reported to have arrhythmogenic potential likely due to its action on the cardiac membranes [4]. A few studies have highlighted the association between QT prolongation and CO poisoning but none of them has reported prolongation to the degree highlighted in the case we present with complete resolution 24 h later [5,6].…”
Section: Introductionmentioning
confidence: 56%
“…Carbon monoxide reduces the oxygen-carrying capacity of blood and binds with cardiac myoglobin, causing a rapid decrease in myocardial oxygen reserves 6 . Several studies have shown that carbon monoxide intoxication causes increased QT intervals and QT dispersion [6][7][8] . This study showed that QTc dispersion and carboxyhemoglobin are signi cantly related.…”
Section: Discussionmentioning
confidence: 99%